Presupposition of Adjectives (Eurasian Scientific Herald, 2022)
In this article, the adjectives are used semantically in the structure of the sentence, refer to the event of presupposition and express a hidden meaning. At the same time, the hidden meaning (presupposition) represented by the adjectives was analyzed through the adjectives